AN EMPIRICAL STUDY OF SMART TECHNOLOGY ADOPTION IN ACADEMIC LIBRARIES: EVIDENCE FROM SELECTED PRIVATE UNIVERSITY LIBRARIES IN THE FEDERAL CAPITAL TERRITORY, ABUJA, NIGERIA - Eke, Ndukwe; Ndukwe, Ogechi; Salihu, Ibrahim; Uppin, Chandrashekhar; Usman, Asmau (FUDMA Journal of Sciences, 2026)
This study examines the adoption and implementation of smart technologies in academic libraries, with a focus on identifying key benefits, challenges, and institutional factors influencing their integration within a developing country context. A mixed-methods approach was employed, combining quantitative and qualitative data collection techniques. Survey data were obtained from 79 respondents across academic libraries, and analyzed using descriptive statistics, while open-ended responses were examined through thematic analysis to identify emerging patterns and insights. The findings reveal that smart technologies, including artificial intelligence (AI), Internet of Things (IoT), and big data analytics, significantly enhance library service delivery, accessibility, and user experience. However, major challenges such as high implementation costs (77.9%), poor infrastructure (53.2%), and limited technical expertise (45.5%) hinder effective adoption. Qualitative results further highlight issues related to user awareness, staff training, and resistance to change. This study is limited by its sample size and geographic focus, which may affect the generalizability of the findings. Future research could expand the scope to include comparative studies across regions and incorporate longitudinal data to assess the long-term impacts of smart technology adoption. It provides actionable insights for academic library managers and policymakers by emphasizing the need for strategic investment, capacity building, and infrastructure development. It also highlights the importance of change management and user engagement in ensuring successful implementation and contributes to the growing body of knowledge on smart libraries by providing empirical evidence from a developing country perspective and integrating quantitative and qualitative insights to offer a comprehensive understanding of adoption dynamics